RISK MANAGEMENT IN SURGICAL CLINICAL UNIT - de Fátima Fernandes Santos Silva, Maria; Siqueira de Oliveira, Rafaela; Janaína de Araújo Silva, Pâmella; Lacerda Jorge Ottoni, Adriana; Juneo Rodrigues Faria, Rogerio; de Oliveira e Silva, Júlia; Luísa Soares da Silva Moreira, Maria; Henrique Santos da Cruz, Guilherme; Dias Gomes, Gabriella; Santos Pereira, Micaela; Paula Nogueira Machado, Ana; Siega Nepomuceno, Matheus; et al. (Health and Society, 2024)
Objective: Identify the health risks patients/workers are exposed to in the surgical clinic of a hospital in the north of Minas Gerais. Method: This is an experience report, the instruments used were: Risk Map – Sector Diagnosis, ANVISA General Standards and Structure Assessment, Risk Mapping Objective: Identify which health risks patients/workers are exposed to from nursing service and Strategic Planning. Results: The risk factors found and highlighted as priorities in the clinical diagnosis of this study were: risk of bleeding, risk of infection, risk of impaired skin integrity, risk of injury, risk of falls, risk of shock and risk of unstable blood glucose. Nurse intervention is of great importance in reducing or even eliminating damage resulting from illness and hospitalization. Conclusion: The study in question provided knowledge to the manager and clinical nurse about the risks that the sector had.